Biocatalysis in the Chemistry of Lupane Triterpenoids - Jan Bachořík (Molecules, 2021)
Pentacyclic triterpenes are important representatives of natural products that exhibit a wide variety of biological activities. These activities suggest that these compounds may represent potential medicines for the treatment of cancer and viral, bacterial, or protozoal infections. Naturally occurring triterpenes usually have several drawbacks, such as limited activity and insufficient solubility and bioavailability; therefore, they need to be modified to obtain compounds suitable for drug development. Modifications can be achieved either by methods of standard organic synthesis or with the use of biocatalysts, such as enzymes or enzyme systems within living organisms. In most cases, these modifications result in the preparation of esters, amides, saponins, or sugar conjugates. Notably, while standard organic synthesis has been heavily used and developed, the use of the latter methodology has been rather limited, but it appears that biocatalysis has recently sparked considerably wider interest within the scientific community. Among triterpenes, derivatives of lupane play important roles. This review therefore summarizes the natural occurrence and sources of lupane triterpenoids, their biosynthesis, and semisynthetic methods that may be used for the production of betulinic acid from abundant and inexpensive betulin. Most importantly, this article compares chemical transformations of lupane triterpenoids with analogous reactions performed by biocatalysts and highlights a large space for the future development of biocatalysis in this field. The results of this study may serve as a summary of the current state of research and demonstrate the potential of the method in future applications.